Celebrating Birthday Based on Weton Calculation by the People of Blitar, East Java - Fahrijal Nurrohman; Habil Abyad (Jurnal Indonesia Sosial Teknologi, 2024)
Javanese society, especially the area that was once under the rule of the Mataram kingdom, has a distinctive calendar. It is the combination of the Saka calendar and the Hijri calendar that gave birth to the Islamic Javanese calendar initiated by Sultan Agung of the Mataram kingdom. One of the interesting things about the Javanese calendar is the weapon. There are several ways of commemorating birthdays based on weton in Blitar society, such as making red and white porridge/jenang, making berkat and doing weton fasting.